Early Intervention in Severe Autism: Positive Outcome Using Exchange and Development Therapy - Blanc, Romuald; Latinus, Marianne; Guidotti, Marco; Adrien, Jean-Louis; Roux, Sylvie; Dansart, Pascale; Barthélémy, Catherine; Rambault, Aude; Bonnet-Brilhault, Frédérique; Malvy, Joëlle (Frontiers in Pediatrics, 2021)
Early intervention programs positively affect key behaviours for children with Autism Spectrum Disorder. Yet, most of these programs do not target children with severe autistic symptomatology associated with intellectual disability (ID). The aim of this study was to investigate psychological and clinical outcomes of children with severe autism and ID enrolled in the Tailored and Inclusive Program for Autism - Tours (TIPA-T). The first step of the TIPA-T is the Exchange and Development Therapy (EDT): an individual neurofunctional intervention, consisting of one-to-one exchanges between a child and a therapist taking place in a pared-down environment. It aims to rehabilitate psychophysiological abilities at the roots of social communication, through structured sequences of “social play”. Cognitive and socio-emotional skills and general development were evaluated with the Social Cognitive Evaluation Battery (SCEB) scale and the Brunet-Lézine scale-Revised, respectively, before and after 9 months of intervention in 32 children with ASD and ID. Autistic symptomatology was evaluated with the Behavior Summarized Evaluation-Revised (BSE-R) scale at 5 time-points in a subset of 14 children, both in individual and group settings. Statistically significant post-intervention improvements were found in cognitive and socio-emotional skills. All but one child showed improvements in at least one social domains, and 78% of children gained one-level in at least 4 social domains. 29 children improved in cognitive domains with 66% of children improving in at least 3 cognitive domains. Autistic symptomatology evaluated in one-to-one settings significantly decreased with therapy; this reduction was observed in more than 85% of children. In group settings, autistic symptomatology also decreased in more than 60% of children. Global developmental age significantly increased by 3.8 months. The TIPA-T, including EDT in particular, improves socio-emotional skills of most children with ASD and reduces autistic symptomatology; yet, with heterogeneous outcomes profiles, in line with the strong heterogeneity of profiles observed in ASD. At the group level, this study highlights the benefits of the TIPA-T for children with severe autism and associated ID. Assessment of autistic core symptoms showed an improvement of social interaction, both in one-to-one and group evaluations, demonstrating the generalizability of the skills learned during the EDT.